PENGARUH ESENSI PROMOSI TERHADAP KEPUTUSAN PEMBELIAN MOBIL MEREK MITSUBISHI XPANDER PADA PT. BOSOWA DI KOTA MAKASSAR - Siti Rahmah; Romansyah Sahabuddin; Muh. Ichwan Musa; Zainal Ruma; Uhud Darmawan Natsir (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to (1) determine the effect of brand awareness on purchasing decisions, (2) determine the effect of brand loyalty on purchasing decisions, (3) determine the influence of brand awareness and brand loyalty jointly on purchasing decisions at PT.Bosowa in Makassar city . The data used in this study are primary and secondary data with a total sample of 83 respondents. This study used a quantitative approach and was analyzed using multiple linear regression analysis with the help of SPSS 25 data processing to prove three hypotheses. The results of this study prove that the Brand Awereness variable has a significant effect on Purchase Decisions with the value of t count > t table where 2.871 > from T table of 1.664. The brand loyalty variable has a significant effect on purchasing decisions because the value of t count > t table is where 2.872 > 1.664. Based on the results of this study it is also known that the independent variables jointly or simultaneously have a significant effect on the dependent variable, namely the purchase decision at PT.Bosowa in Makassar City. Therefore, if Brand Awereness and Brand loyalty are continuously improved, then of course it will improve purchasing decisions to be more optimal.